PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION ( STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III MIS. AL-MUHSININ KECAMATAN RIMBA MELINTANG - Siti Rahma Lingga; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the low result of third grade students learn science MIS. Al-Muhsinin District of Rimba Melintang, with the average - average grade 63.00. While the value of minimum completeness criteria (KKM) IPA is 70, among the students of 20 people only 5 (25.00%) who achieved the KKM. This research is a classroom action research (CAR) conducted aims to improve learning outcomes MIS III grade science students. Al-Muhsinin District of Woods Crossing to implement cooperative learning model STAD (Student Team Achievement Division) data collection instruments in this thesis is the observation sheet activities as well as teacher and student learning outcomes. Improving student learning outcomes can be seen at the base score with an average of 63.25 increased to 72.25 on the daily tests I. The percentage increase from a base score to the daily test I is 14.23%. Deuteronomy daily from I to II daily tests increased 82.00 with the percentage increase in base score to daily test II is 29.64%. On teacher activity has increased in each cycle. Judging from the percentages in the first cycle of the first meeting is 62.50% with both categories, increased in the second meeting be 75.00% with both categories. At the first meeting of the second cycle is 83.33% with very good categories, increased in the second meeting be 87.50% with a very good category. At the student activity also continued to increase in every cycle. The percentage in the first cycle of the first meeting is 62.50% with both categories, increased in the second meeting be 75.00% with both categories. At the first meeting of the second cycle was 79.1% with very good categories, increased in the second meeting be 87.50% with kategoriamat well. The results of this study in class III SD Negeri 19 Muara Dua prove that the implementation of cooperative learning model STAD can improve student learning outcomes Class III MIS. Al-Muhsinin District of Rimba Melintang. Key words: Cooperative Learning Model STAD, Learning Outcomes IPA